Penerapan Pasal 45 Undang Undang Informasi dan Elektronik Terkait Judi Online dalam Perspektif Upaya Penegakan Hukum Terhadap Kejahatan Siber: Penelitian - Gilang Rahadian; Gousta Feriza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The development of information technology has contributed to the increasing incidence of online gambling as a form of cybercrime that adversely affects social order and public morality. This study aims to analyze the application of Article 45 of the Law on Information and Electronic Transactions (ITE Law), particularly the regulatory shift from Article 45 paragraph (2) of Law Number 19 of 2016 to Article 45 paragraph (3) of Law Number 1 of 2024, in the enforcement of online gambling offenses, as well as to examine judicial reasoning from the perspective of justice. This research employs a normative legal research method using statutory, case, and conceptual approaches. The analysis focuses on three court decisions, namely Decision Number 16/Pid.Sus/2024/PN Jakarta Selatan, Decision Number 123/Pid.Sus/2023/PN Payahkumbuh, and Decision Number 575/Pid.B/2025/PN Kisaran. The findings indicate that Article 45 of the ITE Law functions as a lex specialis in addressing online gambling conducted through electronic media and provides a clear legal basis for law enforcement. However, differences in judicial considerations and variations in sentencing were identified among cases with relatively similar offense elements, giving rise to issues of substantive justice, particularly concerning sentencing proportionality and differentiation of offenders’ roles.